The Contribution of EFL Students’ Vocabulary Mastery and Motivation to Writing Ability of Eighth-Grade Students at Smpn 5 Denpasar - Puspitasari, Made; Ratminingsih, Ni Made; Santosa, Made Hery (J-SHMIC : Journal of English for Academic, 2024)
The ability to compose written messages in words, sentences, texts, and coherent words that readers can understand is known as writing ability. The objectives of this research were first to investigate how much the contribution of vocabulary mastery to writing ability, the second was to investigate how much the contribution of motivation to writing ability, and the third was to investigate how much the contribution of vocabulary mastery and motivation simultaneously to writing ability. This study was designed in the form of correlational research design. The population of this study was the eighth-grade students at SMPN 5 Denpasar. In this study, 149 students served as samples. They were chosen using a proportionate random sampling technique. Test of Multiple choice was for vocabulary mastery, questionnaire was for motivation and test of writing assignment was for writing ability, those were utilized to gather the data for this study. With the use of SPSS 26.0, linear and multiple regression analyses were performed on the data. The findings showed that there was high and significant contribution of vocabulary mastery to writing ability. The contribution of vocabulary mastery to writing ability was 69%, and there was high and significant contribution of motivation to writing ability. The contribution of motivation to writing ability was 70.5%. Moreover, the contribution of vocabulary mastery and motivation simultaneously to writing ability was 79.9%. It indicates that there was high and significant contribution of vocabulary mastery and motivation simultaneously to writing ability of eighth grade students of SMPN 5 Denpasar.